Pension reforms and gender equality in Latin America - Arza, Camila (2012)
As most other components in social protection systems, pension schemes can have a substantial impact on gender equality. The way in which pension systems distribute rights, resources and risks can affect men and women differently and serve to mitigate, reproduce or amplify the gender inequalities emerging from the labour market, the distribution of work in the household, etc. Pension systems can also favour some family arrangements over others and introduce incentives that consolidate specific gender roles. Starting with Chile in the 1980s, a number of Latin American countries implemented structural pension reforms that fully or partially replaced these systems with fully funded systems of individual accounts, in which benefits depend on individual pension savings. By strengthening the connection between lifetime contributions and benefits, the new pension schemes raised a whole new set of gender equality issues. More recently, increasing concern about the capacity of women to build sufficient pension savings over their lifetimes to obtain adequate protection in old-age has motivated a number of studies and policy innovations. Some Latin American countries have started to introduce gender-friendly elements in their pension systems to try to improve women's access to social security. This paper evaluates the sources of gender inequality in old-age protection (both institutional and labour market-related) and the way in which recent pension reforms in Latin America have tried to compensate and overcome some of the gender biases in previous systems.